Efficacy of bilateral erector spinae block for intraoperative and post-operative analgesia in lumbar decompression surgeries: A prospective randomized controlled trial - Priyanka G; Chaithali Hebri (Asian Journal of Medical Sciences, 2024)
Background: Lumbar surgery is known to cause severe pain in the post-operative period. Modalities to reduce pain in the perioperative period include opioids, non-steroidal anti-inflammatory drugs, neuraxial blocks, and erector spinae block (ESB). Aims and Objectives: In this study, we aimed to evaluate whether ESB could reduce perioperative pain, opioid consumption, and muscle relaxant consumption. Materials and Methods: Fifty patients scheduled for lumbar decompression spine surgery were randomly allocated to two groups, the erector spinae plane (ESP) group (n=25) and the control group multimodal analgesia group (n=25). Intraoperative hemodynamics, muscle relaxant requirement, opioid consumption post-operative visual analog score, and rescue analgesia were evaluated. Results: Compared with the control group, heart rate (91.24±14.86 and 90.20±14.26) (77.12±11.96 and 77.44±11.96) arterial blood pressures (87.12±8.45 mmHg) (85.25±7.25) (78.73±5.56 and 79.64±5.95) were higher during surgical incision and 1st-time interval than in ESP group, respectively. The visual analog scale scores were higher in the control group than in the ESP group during all measurements of time. The requirement for rescue analgesia was more in the control group compared to the ESP group. Post-operative analgesia lasted for 15–18 h. Conclusion: Ultrasound-guided ESP block is a simple and safe technique which provides effective intraoperative, and post-operative analgesia and patient satisfaction with reduced opioid and muscle relaxant consumption.